Pengaruh Loyalitas dan Citra Merek terhadap Keputusan Pembelian Produk Unilever Pasca Boikot di Jakarta Selatan - Muna Salsabila; Purwatiningsih Purwatiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Marketing management has a strategic role in maintaining the sustainability of the company, especially in the midst of market dynamics and social issues that affect consumer behavior. One of the issues that had an impact was the Boycott, Divestment, and Sanctions (BDS) movement against products that were associated with supporting Israel, including PT Unilever Indonesia Tbk. This study aims to analyze the influence of loyalty and brand image on Unilever product purchase decisions after the boycott in the South Jakarta area. The research method used was quantitative statistics with a survey approach of 100 respondents. Data collection techniques include observation, interviews, and questionnaires. The results of the analysis showed that consumer loyalty had a significant effect on purchasing decisions (Thcal = 3.538 > Ttable = 1.984; sig = 0.001 < 0.05). Brand image also showed significant influence (Thcal = 4.032 > Ttable = 1.984; sig = 0.000 < 0.05). Simultaneously, both variables had a significant effect on purchasing decisions (Fcal = 63.849 > Ftable = 3.09; sig = 0.000). A determination coefficient value (R²) of 0.568 indicates that loyalty and brand image together influence 56.8% of consumer purchase decisions. These findings provide important implications for the company's marketing strategy in responding to social issues and maintaining consumer trust through strengthening loyalty and brand image.